Rancang Bangun Chatbot Pengaduan Kekerasan Perempuan Anak Dengan Metode Fuzzy String Matching Dan Enhanced Confix Stripping Stemmer - Al Muhtadi Billah; Diah Ayu Retnani Wulandari; Yudha Alif Auliya (INFORMAL: Informatics Journal, 2023)
Violence against women is a serious issue affecting many individuals in society. In Indonesia, including Kota Probolinggo, the number of cases of violence against women remains high. This research aims to design a chatbot application as a means for reporting violence against women and children (VAWC) in Kota Probolinggo. The application provides an anonymous and safe space for victims to report their complaints without revealing their identities. Additionally, the chatbot delivers information and education about different types of violence against women and preventive measures. The development of the chatbot application utilizes Fuzzy String Matching, Enhanced Confix Stripping Stemmer, and preprocessing methods to enhance data search accuracy and provide appropriate responses to users. The testing results show that the chatbot offers responses with satisfactory accuracy. Leveraging AI technology in the form of a chatbot is expected to provide an effective solution in addressing and preventing violence against women, offering a secure and anonymous platform for victims to report incidents. The application is envisioned to offer better support and assistance to victims of violence. The chatbot application implements fuzzy string matching, the Levenshtein distance algorithm, and Enhanced Confix Stripping Stemmer to process user input before matching it with the database. During the Enhanced Confix Stripping Stemmer process, sentences are transformed into an array of basic words, enhancing the accuracy of data matching when using fuzzy string matching and the Levenshtein distance algorithm. Testing results indicate a 4.77% difference between manual calculations and the chatbot system. This difference may be attributed to variations in text processing and other factors.